EFFECTIVE METHODS OF TREATING APHTHOUS STOMATITIS AGAINST THE BACKGROUND OF GASTROENTEROLOGICAL DISEASES (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
In modern medical practice, the disease causing irritation of the oral cavity occupies an important place. These diseases become even more complex when they manifest themselves as chronic gastroenterological pathologies. Studies show that patients with chronic gastroduodenitis (CGD) are likely to develop various inflammatory and infectious diseases of the oral cavity. This article presents modern methods and approaches to the treatment of individual chronic recurrent diseases.